Integrated Reporting: Are Indonesian Companies Ready to Do It? - Amelia Setiawan (Emerald Publishing Limited, 2016)
Many companies in Indonesia already have completed sustainability reporting (SR) in their corporate reporting eventhough the regulation has not required public companies to disclose Integrated Reporting (IR) in their report. Are companies with excellent sustainability reporting ready to release integrated reporting? This question is the main concern of this paper. The published guidelines by IIRC are divided into two categories: guidelines which can be assessed objectively and those that cannot be measured objectively. Content analysis is used for data collection and analysis for annual reports of the companies used as sample in this research. The result of this research showed that companies that won Indonesia Sustainability Reporting Award are ready to disclose Integrated Reporting with few modification which adds the value of their report. The implication of the study for public companies is a encouragement to publish integrated reporting and for researchers is being preliminary research for developing research about integrated report in Indonesia.